RANCANG RANCANG BANGUN E-COMMERCE PADA TOKO SEPATU OS DENGAN METODE WATERFALL: METODE WATERFALL - Andih Muhamad Rofi Andih; Resti Amalia (CV. Multi Kreasi Media, 2022)
This research is motivated by the increasing number of trading and service companies that are starting to use the E-Commerce system as an online sales medium. The use of E-Commerce, company information can be conveyed more quickly to customers and a wider marketing reach, so that it is expected to increase sales. This research will design a website-based online promotion and sales media, this design and manufacture is intended to facilitate processing, selling and promotion as well as making it easier for buyers. To make it easier for consumers to choose fashion models, without consumers having to come to the store. Promoting a product must be accompanied by an easy and attractive concept to attract consumers and the public. In the process of building an E-Commerce website, it uses a life cycle development technique or can be called a waterfall. The data flow method used is a structured method consisting of a Data Flow Diagram (DFD) to describe the functional model and an Entity Relationship Diagram (ERD) to describe the data model. The goal to be achieved from the development of this E-Commerce system is to make it easier for buyers to make transactions wherever buyers are without having to come to the OS Store. Keywords: E-Commerce, Shoe Sales, Online store